2019
DOI: 10.13189/ujer.2019.071125
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect of CORE (Connecting, Organizing, Reflecting and Extending) Learning Model on Mathematics Learning Outcomes of Cognitive Domain

Abstract: In the world, mathematics education is one of the fields of study that occupies an important role in creating students who think logically, rational, critical and insightful. Therefore, mathematics is indispensable everyday life and a provision in the face progress of science and technology. This study aimed to assess the effect of the learning model CORE towards mathematics learning outcomes, especially those in the cognitive aspects-this research conducted at Junior High School 34 Pekanbaru with a quasi-expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
4
0
1
Order By: Relevance
“…For the group of students who have been fostered in the ability to Mathematic model in the teaching process, they have solved situations close to teachers' expectations. These findings coincide with those obtained by [16], [17], [18], [19].…”
Section: Discussionsupporting
confidence: 93%
“…For the group of students who have been fostered in the ability to Mathematic model in the teaching process, they have solved situations close to teachers' expectations. These findings coincide with those obtained by [16], [17], [18], [19].…”
Section: Discussionsupporting
confidence: 93%
“…Learners have requirements in different forms of knowledge essential to deal with the question of research, declarative knowledge (facts and concepts), operational knowledge (how to use facts and concepts in the processes or procedures) and strategic understanding) [8] [9]. Most students try hard to resolve complex problems and problem-solving strategies in schools are just the appropriate method or technique to solve organized and algorithmic problems that are taught in schools and universities [10], [11]. Students at the college level also have great difficulties solving problems, while the resolution of problems is an important part of most physics classes.…”
Section: Introductionmentioning
confidence: 99%
“…Bloom's Taxonomy indicates that the classification of effectiveness is in the domain of cognitive, affective, and psychomotor. Concerning our second research question, this study found that mathematics relied upon cognitive domain as it consisted of several aspects: knowledge, comprehension, application, analysis, synthesis, and evaluation which were crucial in learning (Syahtriya Ningsih et al, 2019). Thus, this study discovered significant influence on students' interest through the implementation of AR learning by its ability to apply visualisation in mathematics, while allowing students to keep up with technology advancements.…”
Section: Discussionmentioning
confidence: 84%